A Cross‐National Investigation of the Relationship Between Infant Walking and Language Development. (8th January 2015) - He, Minxuan; Walle, Eric A.; Campos, Joseph J.
<x xml:space="preserve">Abstract</x> The acquisition of walking has recently been linked with infant language development (Walle & Campos, 2014). If this relation reflects the consequence of an epigenetic event, then it should be present regardless of when the infant typically begins to walk, the infant's culture, and the infant's native language. This study sought to replicate the previously reported link between walking and language development in American infants and investigate whether this relation exists cross‐nationally in typically developing Chinese infants exposed to Mandarin. Urban Chinese infants not only provide a distinct linguistic and cultural population in which to study this relation but also typically begin walking approximately 6 weeks later than American infants. Our results demonstrated that (1) walking infants in both the American and Chinese samples had greater receptive and productive vocabularies than same‐aged crawling infants, (2) differences between crawling and walking infants were proportionally similar in each sample, and (3) the walking‐language relation was present for both noun and non‐noun vocabularies. These findings provide further support of a relation between infant walking onset and language development, independent of age. Avenues for future research of the processes involved in this relation, as well as additional populations of interest to investigate, are discussed.